Benevolence – Associations With Stress, Mental Health, and Self-Compassion at the Workplace - Andersson, Christina; Stenfors, Cecilia U. D.; Lilliengren, Peter; Einhorn, Stefan; Osika, Walter (Frontiers in Psychology, 2021)
Objective Benevolence is an emerging concept in motivation theory and research as well as in on pro-social behavior, which has stimulated increasing interest in studying factors that impair or facilitate benevolence and effects thereof. This exploratory study examines the associations between benevolence, stress, mental health, self-compassion, and satisfaction with life in two workplace samples. Methods In the first study n = 522 (38% = female, median age = 42) participants answered questionnaires regarding self-reported stress symptoms (i.e., emotional exhaustion), depressive symptoms and benevolence. In the second study n = 49 (female = 96%) participants answered questionnaires regarding perceived stress, self-compassion, anxiety, depression symptoms, and benevolence. Results In study 1, measures of emotional exhaustion (r = −0.295) and depression (r = −0.190) were significantly negatively correlated with benevolence. In study 2, benevolence was significantly negatively correlated with stress (r = −0.392) and depression (r = −0.310), whereas self-compassion (0.401) was significantly positively correlated with benevolence. While correlations were in expected directions, benevolence was not significantly associated with Satisfaction with Life (r = 0.148) or anxiety (r = −0.199) in study 2. Conclusion Self-assessed benevolence is associated with levels of perceived stress, exhaustion, depression, and self-compassion. Future studies are warranted on how benevolence is related to stress and mental ill health such as depression and anxiety, and if benevolence can be trained in order to decrease stress and mental ill health such as depression and anxiety in workplace settings.